ANALISIS PENGARUH KEBERADAAN PASAR OLEH-OLEH MODERN TERHADAP PENDAPATAN BISNIS ARTSHOP DI KAWASAN SEMINYAK BALI - Setiyana, Khelvin; Widanta, Anak Agung Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 9 (2021): VOL 10 NO 9, SEPTEMBER 2021 [3528 - 3965], 2021)
Economic growth is one of the benchmarks to show the economic development of a region. In the 1990s it became known as the Creative Economy era, an era that not only emphasized the production process alone but also took advantage of the synergy of thinking patterns which produced an output that had high quality, selling value, and aesthetic value. Most of the Creative Economy products are tourism support products, one of which is Artshop. The purpose of this study was to determine the influence of artshop area, business location, length of business, number of customers, and modern markets on the income of the artshop business in the Seminyak area. The sample in this study amounted to 53 respondents with a proportionate random sampling technique. This study uses multiple linear analysis techniques, variable validity test and classical assumption test. Based on the research results, it is concluded that the business area, business location, length of business, number of customers, and modern souvenir markets have an effect on the income of the artshop business in the Seminyak area.   Keywords: Area, Location, Length of Business, Number of Customers, Modern Market, and Income